Determination of film thickness and flooding during reflux condensation in a small, inclined tube with an ultrasonic transducer - Fiedler, S; Yildiz, S; Auracher, H (WILEY, 2003)
The fundamental mechanisms of heat and mass transfer as well as of two-phase flow in compact condensers are not well understood. In this experimental investigation a single sub-channel of a compact plate heat exchanger is simulated by using a small diameter inclined aluminium tube. The inner diameter of the tube is 7 mm and the length is 500 mm. Film thicknesses and flooding points during reflux condensation of steam in this tube are determined by using an ultrasonic technique. Measurements are carried out with a 15 MHz ultrasonic transducer attached to the outer tube wall. The emitted ultrasonic signal is reflected at each interface. The condensate film thickness can be determined by measuring the time difference between the reflections of the signal at the inner tube wall and at the liquid-vapour interface. The results for the liquid film thickness obtained by the pulse-echo technique are compared with those obtained by a needle-probe technique. As the measured film thicknesses were found to be in good agreement, the accuracy of the pulse-echo technique could be verified. The results demonstrate that the ultrasonic pulse-echo technique offers a feasible alternative for two-phase flow applications. With the pulse-echo technique the thickness of the condensate film was measured at the lowermost point of the tube. The film thickness measurements were carried out before the onset of flooding at inclination angles of 30, 60 and 90degrees to the horizontal. It was found that the inclination angle has only a minor effect on the film thickness. Shear stress and surface tension have in small diameter tubes apparently a more obvious effect than the gravitational force. The flooding experiments are carried out at a pressure of 10 kPa and at inclination angles of 30, 60 and 90degrees to the horizontal. The results show that the inclination angle has no significant effect on the onset of flooding in the small diameter tube. A modified form of a flooding correlation proposed by McQuillan and Whalley is presented. This correlation predicts well the experimental data. Copyright (C) 2003 John Wiley Sons, Ltd.
Keywords: reflux condensation; compact condensers; flooding; inclined tube; film thickness measurement; ultrasonic pulse-echo technique; COUNTERCURRENT-FLOW; PIPES; Energy & Fuels; Nuclear Science & Technology